2018
DOI: 10.1002/uog.18830
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fetal movements and cerebroplacental ratio: evidence for worsening fetal hypoxemia

Abstract: Pregnancies complicated by multiple episodes of RFM show significantly lower CPR MoM and MCA-PI MoM compared with those with single episodes and controls. This is likely to be due to worsening fetal hypoxemia in women presenting with recurrent RFM. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
0
25
1
Order By: Relevance
“…Our finding that SGA is not more common in women with recurrent RFM is at odds with O'Sullivan et al, and with Scala et al, who found a far higher (44.2% vs 9.8%) proportion of SGA (unstated reference chart) babies in the multiple episodes group . Despite this, using an overlapping but larger cohort, Binder et al demonstrated no difference in birthweight centile or incidence of SGA between pregnancies with single or multiple episodes . They did record however, a small increase (5.9%‐7.8%) in a low (<5th centile) cerebroplacental ratio and a decrease in cerebroplacental ratio multiples of the median in women with multiple episodes.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Our finding that SGA is not more common in women with recurrent RFM is at odds with O'Sullivan et al, and with Scala et al, who found a far higher (44.2% vs 9.8%) proportion of SGA (unstated reference chart) babies in the multiple episodes group . Despite this, using an overlapping but larger cohort, Binder et al demonstrated no difference in birthweight centile or incidence of SGA between pregnancies with single or multiple episodes . They did record however, a small increase (5.9%‐7.8%) in a low (<5th centile) cerebroplacental ratio and a decrease in cerebroplacental ratio multiples of the median in women with multiple episodes.…”
Section: Discussioncontrasting
confidence: 50%
“…The incidence of RFM is relatively high; particularly, the proportion of women who present more than once (46%), which is higher than what has been previously reported . It is possible that this is in part a result of a current and ongoing national awareness campaign in the UK…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…One case‐control study, Warrander et al , reported that median (range) BMI was not significantly different between women who presented with DFM and gave birth within 7 days ( n = 36) and women without DFM ( n = 36) (24.4, 18.1–45.6 kg/m 2 vs. 24.6, 17.8–41.6 kg/m 2 , p = 0.88) . Another case‐control study, Binder et al, reported median [interquartile range (IQR)] BMI of 24.6 (IQR 21.9–28.3) kg/m 2 in DFM cases ( n = 4500), which was not significantly different ( p = 0.40) from the median (IQR) BMI of 24.5 (IQR, 22.0–28.78) kg/m 2 in controls ( n = 1527) . In contrast, Pagani et al , reported that women presenting with DFM ( n = 742) had significantly higher median (IQR) BMI than control women ( n = 16 907, 24.2, IQR 21.8–28.3 kg/m 2 vs. 23.5, IQR 21.2–26.7 kg/m 2 , p ≤ 0.001).…”
Section: Resultsmentioning
confidence: 99%